2020
DOI: 10.21203/rs.2.23283/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bile cholesterol and viscosity, the keys to discriminating adenomatous polyps from cholesterol polyps by a novel predictive scoring model.

Abstract: Abstract Background: Adenomatous gallbladder polyps, premalignant lesions of the gallbladder, have fatal outcomes, whereas cholesterol polyps have benign features. Herein, we proposed a novel, predictive scoring model of adenomatous polyps to distinguish them from cholesterol polyps, by analyzing bile components and bile viscosity. Methods: Patients with gallbladder polyp pathologically confirmed after cholecystectomies were analyzed. After dividing patients into two gr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Concerning increased body weight, several studies which set non-polyp subjects as the control group found this to be associated with GPs [14,37,38]. Interestingly, the positive relationship was hardly reported in other studies which compared CPs with neoplastic polyps as controls [12,19,39]. Indeed, it is well known that CPs and neoplasms progress in entirely different pathological processes, and this inconsistency needs more research to con rm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning increased body weight, several studies which set non-polyp subjects as the control group found this to be associated with GPs [14,37,38]. Interestingly, the positive relationship was hardly reported in other studies which compared CPs with neoplastic polyps as controls [12,19,39]. Indeed, it is well known that CPs and neoplasms progress in entirely different pathological processes, and this inconsistency needs more research to con rm.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have profoundly investigated the risk factors for GPs formation, including middle age, male gender, obesity, fatty liver, abnormal body fat distribution, and dyslipidemia, but most of them were based on ultrasound results rather than specifying the exact histological classi cation [9][10][11]. Given that risk factors and the mechanisms of pathophysiologic mechanisms are quite different in various GPs, pathology-oriented analysis is undoubtedly more convincing [12]. However, so far, there is a paucity of data from high-level studies lucubrating CPs [13,14].…”
Section: Introductionmentioning
confidence: 99%